Business Strategy Decision-Making Model in Efforts to Increase Sales of Bakery Industry MSMEs in Lampung Province - Niki Agus Santoso; Trenggono Pujo Sakti; Dora Rinova (Sanskara Manajemen Dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the bakery industry have an important role in supporting regional economic growth, especially in Lampung Province. However, many bakery MSMEs still face difficulties in achieving optimal sales targets due to ineffective implementation of business strategies. This study aims to analyze the priority of business strategy decision-making for increasing sales among bakery MSMEs in Lampung Province using the Soft Systems Methodology (SSM) and the Analytical Hierarchy Process (AHP). This research uses a descriptive qualitative approach, combining library and field research methods through interviews, observations, and questionnaires, involving MSME owners, operational managers, marketing managers, academics, and business practitioners. The results show that the main priority strategy is opening new outlets with a weight value of 0.330, followed by product innovation (0.279), creating attractive social media content (0.226), and improving service quality (0.165). These findings indicate that business expansion through strategic outlet development is the most effective way to improve sales performance. This research is expected to provide both theoretical and practical contributions for the development of bakery MSMEs in Lampung Province.